Zeitmaschine, Oder : Das Museum in Bewegung. - Beil, Ralf; Born, Karl Ludwig; Gachnang, Johannes; Gertsch, Franz; Grigely, Joseph; Grünbein, Durs; Lichtin, Christoph; Opitz, Martin; Oppenheim, Meret; Reust, Hans Rudolf; Roth, Dieter; Schneemann, Peter J.; et al. (Ostfildern-Ruit : Hatje Cantz Verlag, 2002)
Anders, Anna ; Anker, Albert ; Araki, Nobuyoshi ; Beuys, Joseph ; Böcklin, Arnold ; Brand, Heinz ; Burgkmair, Hans ; Burkhard, Balthasar ; Byars, James Lee ; Canova, Antonio ; Christo ; Coste, Annelise ; Delaunay, Robert ; Derain, André ; Dijkstra, Rineke ; Disler, Martin ; Fischli, Peter ; Weiss, David ; Fisher, Joel ; Frecon, Suzan ; Gertsch, Franz ; Hahn, Alexander ; Hanny, Karl ; Hirschhorn, Thomas ; Hodel, Ernst ; Hodler, Ferdinand ; Hofer, Andreas ; Huber, Felix Stephan ; Huws, Bethan ; Ikemura, Leiko ; Jawlensky, Alexej von ; Kabakov, Ilya ; Klee, Paul ; Klingelhöller, Harald ; König, Franz Niklaus ; Macke, August ; Marc, Franz ; Marclay, Christian ; Michel, Eugen ; Moilliet, Louis ; Nussbaum, Guido ; Oppenheim, Meret ; Pettibon, Raymond ; Polke, Sigmar ; Richter, Gerhard ; Pozarek, Vaclav ; Raetz, Markus ; Roth, Dieter ; Rütimann, Christoph ; Schiess, Adrian ; Schnyder, Jean-Frederic ; Schütte, Thomas ; Schwitters, Kurt ; Smith, Stephanie ; Stewart, Edward ; Spoerri, Daniel ; Strba, Annelies ; Struth, Thomas ; Tuymans, Luc ; West, Franz ; West, Cécile ; Wölfli, Adolf
Duits
Zeitmaschine, Oder : Das Museum in Bewegung, Kunstmuseum Bern, 22. März bis 21. Juli 2002
boek